2001
DOI: 10.1152/ajpendo.2001.280.3.e509
|View full text |Cite
|
Sign up to set email alerts
|

Arginine and ornithine kinetics in severely burned patients: increased rate of arginine disposal

Abstract: Arginine serves multiple roles in the pathophysiological response to burn injury. Our previous studies in burn patients demonstrated a limited net rate of arginine de novo synthesis despite a significantly increased arginine turnover (flux), suggesting that this amino acid is a conditionally indispensable amino acid after major burns. This study used [15N2-guanidino-5,5-2H2]arginine and [5-13C]ornithine as tracers to assess the rate of arginine disposal via its conversion to and subsequent oxidation of ornithi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 37 publications
(69 reference statements)
5
42
0
Order By: Relevance
“…Our tentative conclusion concerning the dietary dispensability of arginine applies only to healthy subjects and with nutritional balance as an endpoint; we have previously concluded that a source of dietary arginine is required in severely stressed patients 16 and so in this case arginine is a conditionally indispensable amino acid.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our tentative conclusion concerning the dietary dispensability of arginine applies only to healthy subjects and with nutritional balance as an endpoint; we have previously concluded that a source of dietary arginine is required in severely stressed patients 16 and so in this case arginine is a conditionally indispensable amino acid.…”
Section: Discussionmentioning
confidence: 82%
“…8 The 13 C retention factor for estimating arginine oxidation was obtained from 6 healthy subjects receiving a constant infusion of L-[5-13 C]glutamic acid. 16 These studies gave a fractional recovery of 13 CO 2 of 0.40 and 0.52, respectively, for fasting and fed states in healthy subjects. L-[5-13 C]glutamic acid was used to determine fractional retention of 13 C, because its 13 C carbon is a more direct precursor for estimation of arginine oxidation, than bicarbonate or acetate.…”
Section: Tracer Model Of Amino Acid Kineticsmentioning
confidence: 94%
“…Such production should be accompanied by a higher rate of arginine and glutamine fluxes. As mentioned above, the synthesis of ornithine from arginine is increased in burn patients (Yu et al 2001). From the few studies on arginine metabolism in patients, it appears that arginine is mainly lost by degradation in the urea cycle.…”
Section: Nitrogen Eliminationmentioning
confidence: 89%
“…Arginine is also produced by the intestine from glutamate (Reeds 2000). In humans, use of plasma kinetics has provided an unclear picture to whether endogenous arginine synthesis is modified in inflammatory states (Castillo et al 1995;Yu et al 1995aYu et al , 2001). In contrast, arginine production by the portal drained viscera was increased during endotoxemia in pigs (Bruins et al 2000).…”
Section: Synthesis De Novomentioning
confidence: 99%
See 1 more Smart Citation